The Effect of Language Dominance on the Selective Attention of Segments and Tones in Urdu-Cantonese Speakers - Liu, Yi; Ning, Jinghong (Frontiers in Psychology, 2021)
To perceive a second language (L2), non-native speakers not only have to focus on phonological, lexical and grammatical knowledge, but also need to develop a good mastery of L2 strategic knowledge, including selective attention and language planning. Previous research has found that non-tonal speakers are overtly attentive to segments, while tonal language speakers give more attention to tones. However, it is unclear how different dominant language speakers distribute their attention while processing both. segments or tones and segments and tones stimuli in non-native speeches. The present study also aims to examine the roles of language dominance play in the designed perceptual tasks. In the current study 20 Cantonese native speakers, 18 Cantonese-dominants, and 18 Urdu-dominants participated in an attention distribution experiment in Cantonese. The results show that the Urdu-dominants retain their L1 attentional strategy in the processing of Cantonese stimuli, classifying the stimuli along segments, while the Cantonese native speakers are more attentive to tones. Moreover, the Cantonese-dominants show a perceptual flexibility as highly proficient and experienced listeners. The results reveal that language dominance plays a vital role in listeners’ attention distribution. The research also supports PAM-L2’s hypothesis theory on bilinguals, proposed by Antoniou, Tyler and Best (2012). The findings of the current study can be applied to Chinese language learning and teaching and language acquisition studies.